2011
DOI: 10.4028/www.scientific.net/amr.396-398.2366
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antioxidant and Antibacterial Activities of Salicylaldehyde Azine

Abstract: Salicylaldehyde azine (SA) were synthesized with salicylaldehyde and hydrazine hydrate as a raw material. The crystal structure was characterized by X-ray diffraction, as well as the total antioxidant capacity and antibacterial activities against Staphylococcus aureus and Escherichia coli were investigated. It was found that SA exhibited significant antibacterial activities and total antioxidant capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In an exhaustive literature survey of the reaction product(s) of ester 1 and hydrazine hydrate, bearing in consideration the possible ring-openings of chromene-2-ones [ 37 ], Soliman et al [ 38 ] described, in 1985, the reaction of ethyl 2-oxo-2 H -chromene-3-carboxylate ( 1 ) with hydrazine hydrate in refluxing ethanol, in which they obtained salicylaldehyde azine ( 3 ) in 31.5% and 42.4% yields for one and two equivalent of hydrazine hydrate, respectively, instead of the claimed hydrazide 2 . The structure of the well-known and commercially available salicylaldehyde azine ( 3 ), was rigorously proven by independent synthesis using the reaction of salicylaldehyde with hydrazine hydrate [ 39 ]. Comparison of the melting point and spectral data for an authentic sample of compound 3 and the yellow crystals produced in our trials, gave us absolute confidence to assign the structure of these crystals to be salicylaldehyde azine ( 3 ), in complete agreement with the results of Soliman and his co-workers ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an exhaustive literature survey of the reaction product(s) of ester 1 and hydrazine hydrate, bearing in consideration the possible ring-openings of chromene-2-ones [ 37 ], Soliman et al [ 38 ] described, in 1985, the reaction of ethyl 2-oxo-2 H -chromene-3-carboxylate ( 1 ) with hydrazine hydrate in refluxing ethanol, in which they obtained salicylaldehyde azine ( 3 ) in 31.5% and 42.4% yields for one and two equivalent of hydrazine hydrate, respectively, instead of the claimed hydrazide 2 . The structure of the well-known and commercially available salicylaldehyde azine ( 3 ), was rigorously proven by independent synthesis using the reaction of salicylaldehyde with hydrazine hydrate [ 39 ]. Comparison of the melting point and spectral data for an authentic sample of compound 3 and the yellow crystals produced in our trials, gave us absolute confidence to assign the structure of these crystals to be salicylaldehyde azine ( 3 ), in complete agreement with the results of Soliman and his co-workers ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A mixture of ethyl 2-oxo-2 H -chromene-3-carboxylate ( 1 , 2.18 g, 10 mmol) and hydrazine hydrate, (99%, 1.3 g, 25 mmol) in absolute ethanol (50 mL) was heated under reflux for 2 h. The precipitate formed was filtered off, washed with ethanol and dried. Recrystallization from ethanol gave yellow crystalsof salicyaldehyde azine ( 3 ) [ 38 , 39 ] (1.15 g, 48%); m.p. 205–206 °C (204.3 °C) [ 39 ]; IR ν 3350–2830 (OH), 1633 (C=N) cm −1 ; 1 H-NMR δ 6.84–7.72 (m, 8H, ArH), 8.86 (s, 2H, –CH=), 10.90 (s, D 2 O exch., 2H, OH); 13 C-NMR δ 117.9, 118.7, 121.4, 132.0, 132.5, 159.2, 162.0; MS m/z : 240.5 (M + ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Some uorescent compounds have been successfully synthesized to overcome this disadvantage such as polythiophene and its derivatives, 18,19 as well as tetraphenylethene derivatives, 20 1methyl-1,2,3,4,5-pentaphenylsilole, 21 and p-sexiphenyl. 22 Concurrently, some studies on salicylaldehyde azines have been reported including pharmacological proprieties 23,24 and optical properties. 25,26 The AIE characteristic of salicylaldehyde azine was rst fully studied by Tang.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical properties and biological activities of these compounds mostly are the consequence of the presence of double bonds and nitrogen atoms. It is well known that they possess antibacterial (Veena et al, 2011;Chourasiya et al, 2015), antifungal (Kurteva et al, 2011), anticonvulsant (Gul et al, 2004), antineuroinflammatory (Subedi et al, 2017), anticancer (Krezel et al, 1999;Qian et al, 2010;Liang et al, 2014) and antioxidant (Li et al, 2011) activities. Also, they behave as aldose reductase inhibitors (Meanwell et al, 1991) and MDR reversal agents (Paterna et al, 2018).…”
Section: Introductionmentioning
confidence: 99%